A comparison of the effect of soaking in 75% pomegranate peel and pulp extract versus sodium hypochlorite on the surface roughness of heat-cured acrylic resin denture bases - Watri, Desi; Wijaya, Cindy Denhara; Harahap, Fitriah Khairani; Pakpahan, Sadesma Uli; Oktavia, Yuli; Sitio, Annisa Rizqi Ramadhani (Buletin Kedokteran & Kesehatan Prima, 2025)
Heat-cured acrylic resin is the most common material used for denture bases; however, it has limitations such as susceptibility to fluid absorption and abrasion, which can increase surface roughness. This roughness has the potential to become a site for the colonisation of microorganisms such as Candida albicans. Sodium hypochlorite is frequently used as a denture disinfectant, but its corrosive properties can exacerbate surface roughness. Therefore, alternative natural materials such as pomegranate (both peel and pulp) extracts have become a focus of research. Aim: This study aimed to determine the comparative effects of immersion in 75% pomegranate peel extract and 75% pomegranate pulp extract versus sodium hypochlorite on the surface roughness of heat-cured acrylic resin. Method: This study employed a pre- and post-test control group experimental laboratory design, with three treatment groups of nine samples each. Acrylic resin samples were immersed for 7 days and 14.5 hours in the treatment solutions, and their surface roughness was measured using a surface roughness tester before and after immersion. Data analysis was performed using the Shapiro-Wilk test, One-Way ANOVA, and Post Hoc Tukey test. Results: This study found no significant difference between the treatment groups regarding the surface roughness of heat-cured acrylic resin (p = 0.718). However, only the sodium hypochlorite group showed a significant change in surface roughness before and after immersion (p = 0.003), whereas the pomegranate peel and pulp extract groups did not show significant changes (p = 0.099 and p = 0.065, respectively). Conclusion: 75% pomegranate peel and pulp extracts did not cause significant changes to the surface roughness of heat-cured acrylic resin and may represent safer natural alternatives to sodium hypochlorite as denture soaking solutions.